Computed tomography abnormalities antedating mesothelioma diagnosis: a perspective on the natural history. Issue 2 (28th February 2019) - Hassan, Maged; Tsikrika, Stamatoula; Asciak, Rachelle; Mercer, Rachel M.; El-Ganady, Anwar; Rahman, Najib M.
Malignant pleural mesothelioma (MPM) is an aggressive and fatal disease that typically presents with breathlessness, chest pain or both [1]. It is usually a unilateral disease but 3% of patients have malignant disease bilaterally at presentation [2]. The latency period between exposure to asbestos and MPM development is 20–40 years. Radiological evolution of MPM is difficult to infer. Previous pleural effusion or thickening warrants careful follow-up. Some patients don't exhibit abnormalities a few months prior to diagnosis while others carry pleural abnormalities for several years. http://ow.ly/uTGO30mJ8D2